Carbon fiber bundle, tow-impregnated material, carbon fiber-reinforced composite material, pressure vessel, and method for producing carbon fiber bundle

By controlling the fiber fineness of the carbon fiber precursor fiber and the tensile ratio in the process, the problem of difficulty in simultaneously improving the tensile strength, tensile elastic modulus and mass changes in the prior art is solved, and the production of high-performance carbon fiber bundles is achieved.

CN119654455APending Publication Date: 2025-03-18TORAY INDUSTRIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380057954.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-24
Filing Date
2023-08-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve tensile strength, tensile elastic modulus, and reduce mass variation per unit length in the fiber length direction in the carbon fiber.

Method used

By controlling the fibrousness of the carbon fiber precursor fiber, the stretch ratio of the wire making process and the flame-resistant process, high-performance production of carbon fiber bundles is achieved. The specific method includes performing two-stage flame resistance treatment in the flame resistance step, and controlling the crystal orientation and blackening thickness of the carbon fiber during the heat treatment process.

Benefits of technology

The excellent tensile strength and tensile elastic modulus of the resin-impregnated wire harness of the carbon fiber bundle are achieved, while reducing the mass change per unit length in the fiber length direction, ensuring the stability and high performance of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005262029490000231
    Figure BDA0005262029490000231
Patent Text Reader

Abstract

The present invention addresses the problem of providing a carbon fiber bundle having excellent tensile strength and tensile modulus of a resin-impregnated wire harness, the carbon fiber bundle having little variation in mass (g / m) per unit length of the carbon fiber bundle. In order to solve this problem, provided is a carbon fiber bundle in which the strength of a resin-impregnated wire bundle is 4.5-6.5 GPa, the elastic modulus of the resin-impregnated wire bundle is 205-270 GPa, the number of filaments is 6,000-36,000, and the coefficient of variation of the mass (g / m) per unit length of the carbon fiber bundle, expressed by the ratio of the standard deviation to the average value, is 0.00-0.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon fiber bundle suitable for fiber reinforced plastics, a bundle impregnation material, a carbon fiber reinforced composite material and a pressure vessel, and a method for manufacturing the carbon fiber bundle. Background Art

[0002] As environmental issues continue to become more prominent, the use of carbon fiber as a reinforcing fiber for composite materials is expanding in various aspects, and there is a strong demand for further high performance and high quality. Improving the mechanical properties of carbon fiber helps to reduce the weight of components such as pressure vessels, so it is important to improve mechanical properties such as tensile strength and tensile modulus. At the same time, from the perspective of stabilizing the quality of the final component, reducing fuzz and reducing the variation of unit area weight, such as the grade of carbon fiber, has also become an important issue. In brittle materials such as carbon fiber, the defect size can be reduced or the fracture toughness value can be increased according to the Griffith formula, thereby improving, for example, tensile strength. In particular, the improvement of the fracture toughness value is effective in terms of being able to increase tensile strength independently of the state of the defect size (Patent Document 1). In order to evenly improve mechanical properties such as tensile strength and tensile modulus, it is also important to eliminate the internal and external structural differences existing in the cross section of a single fiber.

[0003] As methods for suppressing the difference in internal and external structures of a single fiber cross section and improving performance, for example, the following methods have been proposed: during flame retardant treatment, flame retardant treatment is carried out in a liquid phase, thereby shortening the flame retardant treatment time and improving the performance of the carbon fiber; in a flame retardant treatment furnace composed of a plurality of furnaces, the residence time of each furnace is adapted to the density of the carbon fiber precursor fiber to increase the flame retardant treatment temperature; and a method of adjusting the flame retardant treatment atmosphere (patent documents 2 to 4).

[0004] In Patent Documents 3 and 4, the temperature control area of ​​the flame retardant process is set to 2 to 3 zones, and the internal and external structural differences of the flame retardant fiber are controlled by controlling the specific gravity increase rate relative to the flame retardant time and the flame retardant temperature control relative to the specific gravity. The tensile modulus can be improved by orienting the structure of the formed fiber along the fiber axis. Therefore, as a method for improving the tensile modulus, a method of stretching in the coagulation process in the spinning process and a method of stretching in the flame retardant process in the sintering process are proposed (Patent Documents 5 and 6).

[0005] In addition, in order to stably reflect the mechanical properties of carbon fibers in composite materials, it is necessary to suppress the variation of the unit area weight of carbon fibers. For example, as a method for stabilizing the unit area weight of a tow preg, a method for manufacturing a tow preg by measuring the unit area weight of each fiber bundle before impregnation and combining the fiber bundles so that the fiber unit area weight falls within a specified range is proposed (Patent Document 7).

[0006] In the filament winding (hereinafter sometimes referred to as "FW") method and the automatic lamination method, which are molding methods for carbon fiber reinforced composite materials, FRP is manufactured using one or a limited number of strip-shaped unidirectional prepreg blanks. Therefore, if the deviation in the unit area weight between the strip-shaped unidirectional prepreg blanks is large, the total weight when the strip-shaped unidirectional prepreg blanks are made into FRP will deviate, and the thickness of each part will deviate from the designed thickness. Although such a problem exists, it can be solved.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 97 / 45576

[0010] Patent Document 2: Japanese Patent Application Publication No. 2004-300600

[0011] Patent Document 3: Japanese Patent Application Publication No. 2006-283225

[0012] Patent Document 4: Japanese Patent Application Publication No. 2017-66580

[0013] Patent Document 5: Japanese Patent Application Publication No. 2009-079343

[0014] Patent Document 6: International Publication No. 2008 / 063886

[0015] Patent Document 7: Japanese Patent Application No. 2022-519335 Summary of the invention

[0016] Problems to be solved by the invention

[0017] However, Patent Document 1 only controls the single fiber fineness and the internal and external structure difference to achieve physical property improvement based on surface defect control or fine structure distribution control of carbon fiber, but does not achieve improvement in the variation of mass per unit length (g / m).

[0018] Patent Documents 2 to 4 focus on the heating temperature and time in the flame retardant step to improve the quality of carbon fiber, but do not focus on the drawing ratio in the calcining step and the spinning step, and do not achieve improvement in the variation of the mass per unit length (g / m).

[0019] In Patent Document 5, steam stretching is omitted and instead, the orientation degree of the raw yarn is increased by performing high stretching in the coagulation process, thereby making it easier to exhibit the tensile elastic modulus. However, as far as the temperature control of the flame retardant process is concerned, the stretching amount is not controlled, including in the firing process, so the variation of the mass per unit length (g / m) is likely to become larger.

[0020] Patent Document 6 shows high strand strength and elastic modulus by high stretching in the flame retardant process, but it is limited to carbon fibers with small fineness and does not intend to apply stretching and temperature control in the flame retardant process to carbon fibers with large fineness.

[0021] In addition, Patent Document 7 uses a method of manufacturing a tow preg by combining a plurality of fiber bundles, but there is a problem that this method cannot be applied when processing using a single fiber bundle.

[0022] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a carbon fiber bundle having a small variation in mass per unit length (g / m) in the fiber length direction and having excellent resin-impregnated strand tensile strength and resin-impregnated strand tensile elastic modulus.

[0023] Means for solving problems

[0024] The inventors of the present application have discovered the following method, thereby completing the present invention, namely, while increasing the fineness of carbon fiber precursor fibers to improve productivity, by improving the control of the internal and external structural differences of single fibers and controlling the stretching ratios in the spinning process and the flame retardant process, a carbon fiber bundle is obtained that simultaneously achieves tensile strength and elastic modulus and reduces the variation in mass (g / m) per unit length in the fiber length direction at a level that has not been achieved by conventional carbon fiber bundles.

[0025] In order to achieve the above-mentioned object, the carbon fiber bundle of the present invention has the following characteristics.

[0026] (1) A carbon fiber bundle, wherein the resin-impregnated bundle has a tensile strength of 4.5 to 6.5 GPa, a tensile elastic modulus of 205 to 270 GPa, the number of filaments is 6,000 to 36,000, and the coefficient of variation of the mass per unit length (g / m) of the carbon fiber bundle, represented by the ratio of the standard deviation to the average value ([standard deviation] / [average value]×100(%)), is 0.00 to 0.5%.

[0027] (2) The carbon fiber bundle according to (1), wherein an average single fiber diameter d (unit: μm) of the carbon fibers is 6.0 μm or more and less than 8.0 μm, and

[0028] The blackened thickness K (unit: μm) of the carbon fiber is 0.38×d or more, and

[0029] The degree of crystal orientation π of the carbon fiber bundle is 79.5% or more.

[0030] (3) The carbon fiber bundle according to (1) or (2), wherein Rr is 1.03 or less, when Rr is a ratio (Ri / Ro) of the crystallinity Ri of the inner layer to the crystallinity Ro of the outer layer of the single fiber obtained by Raman spectroscopy.

[0031] (4) The carbon fiber bundle according to any one of (1) to (3), wherein the number of fuzz in the carbon fiber bundle when unwinding is 1.5 pieces / m or less.

[0032] (5) A tow preg using the carbon fiber bundle according to any one of (1) to (4).

[0033] (6) A carbon fiber reinforced composite material using the carbon fiber bundle according to any one of (1) to (4).

[0034] (7) A pressure vessel using the carbon fiber bundle according to any one of (1) to (4).

[0035] (8) A method for producing a carbon fiber bundle, which is a method for producing a carbon fiber bundle described in any one of (1) to (4) above, wherein a carbon fiber precursor fiber bundle having a single fiber fineness of 1.4 to 3.4 dtex is stretched at a stretch ratio of 1.30 to 3.00 while being subjected to a flame retardant treatment to obtain a flame retardant fiber bundle, and then the flame retardant fiber bundle is heat treated at 1,200 to 3,000°C in an inert atmosphere to obtain a carbon fiber bundle.

[0036] (9) The method for producing a carbon fiber bundle according to (8), wherein the flame retardant treatment comprises two steps of treatment, and in the first flame retardant treatment step, the carbon fiber bundle is treated to a wavelength of 1,453 cm in the infrared spectrum. -1 The peak intensity relative to 1,370 cm -1 The flame retardant treatment is performed until the ratio of the peak intensity of the infrared spectrum to the peak intensity of the infrared spectrum is within the range of 0.74 to 0.80. In the second flame retardant treatment step performed later than the first flame retardant treatment step, the peak intensity of the infrared spectrum is 1,453 cm -1 The peak intensity relative to 1,370 cm -1 The peak intensity ratio of 1,254 cm-1 in the infrared spectrum is in the range of 0.60 to 0.65. -1 Peak intensity relative to 1,370 cm -1 The flame retardant treatment is performed until the ratio of the peak intensity of the carbon fiber to the carbon fiber falls within the range of 0.70 to 0.80, and the flame retardant fiber bundle obtained by the flame retardant treatment is heat-treated at 1,200 to 3,000° C. in an inert atmosphere to obtain a carbon fiber bundle.

[0037] Effects of the Invention

[0038] According to the present invention, the following carbon fiber bundle can be obtained: even if a carbon fiber precursor fiber bundle having a large fineness and high productivity is used, by controlling the stretching in the spinning process and the flame retardant process, a high-performance carbon fiber reinforced composite material can be obtained that has excellent stability in the fiber content during composite material molding and exhibits excellent tensile strength and tensile elastic modulus. DETAILED DESCRIPTION

[0039] The number of filaments of the carbon fiber bundle of the present invention is 6,000 or more, preferably 12,000 or more. When the FW method is used to manufacture a composite material, the productivity depends on the yarn speed and the number of filaments, so the composite material can be efficiently manufactured by a large number of filaments. If the number of filaments is 6,000 or more, it can meet the viewpoint of productivity. The upper limit of the number of filaments is not particularly limited. The more filaments there are, the easier it is to produce a deviation in the mass (g / m) per unit length caused by uneven stretching inside and outside the filament bundle in the stretching process. Therefore, the number of filaments is preferably 36,000 or less.

[0040] The resin-impregnated bundle tensile strength of the carbon fiber bundle of the present invention (sometimes also referred to as "bundle strength") is 4.5 GPa or more, preferably 5.3 GPa or more, and more preferably 5.5 GPa or more. If the bundle strength is 4.5 GPa or more, the carbon fiber bundle has the potential to exhibit good tensile strength when used to manufacture composite materials. It should be noted that the bundle strength can be obtained by the method described in the bundle tensile test of the carbon fiber bundle described later. There is no particular upper limit on the bundle strength, but from the perspective of productivity, it is usually 6.5 GPa or less.

[0041] The resin-impregnated bundle tensile modulus of the carbon fiber bundle of the present invention (sometimes also referred to as "bundle elastic modulus") is 205 to 270 GPa, preferably 212 to 260 GPa, and more preferably 217 to 255 GPa. If the bundle elastic modulus is 205 to 270 GPa, the balance between the bundle elastic modulus and the bundle strength is excellent, so it is preferred, especially by controlling the bundle elastic modulus to 212 to 260 GPa, so that a carbon fiber bundle with excellent bundle strength can be easily obtained. It should be noted that the bundle elastic modulus can be obtained by the method described in the bundle tensile test of the carbon fiber bundle described later. The bundle elastic modulus can be mainly controlled by applying tension to the fiber bundle in any heat treatment process in the manufacturing process of the carbon fiber bundle, or by changing the carbonization temperature.

[0042] In addition, for the carbon fiber bundle of the present invention, when the mass per unit length of the carbon fiber bundle (mass per 1m length (g). The unit is g / m), the coefficient of variation (%) represented by the ratio of the standard deviation to the average value ([standard deviation] / [average value]×100(%)) (hereinafter, sometimes simply referred to as "the coefficient of variation of the mass per unit length of the carbon fiber bundle") is 0.00 to 0.5%. As an upper limit, it is preferably 0.4% or less, and more preferably 0.25% or less. As the lower limit of the coefficient of variation of the mass per unit length of the carbon fiber bundle, it is most preferably 0.00%, but from the viewpoint of productivity and practicality, as long as it is 0.05% or more and 0.5% or less, a balance between cost and performance can be achieved.

[0043] When manufacturing a pressure vessel by FW molding, even for carbon fibers with the same strand strength, stress concentration occurs at the lowest mass per unit length (g / m) among the deviations in stress burden, and fracture easily begins. Therefore, when the coefficient of variation of the mass per unit length of the carbon fiber bundle is large, even if the average strand strength is high, the amount of carbon fiber bundle used has to be increased in proportion to the assumed strength utilization rate. Therefore, for example, when the carbon fiber bundle is used for a pressure vessel, the mass of the tank increases, but by suppressing the coefficient of variation of the mass per unit length of the carbon fiber bundle, the amount of carbon fiber bundle used can be suppressed, and further weight reduction of the composite material can be achieved.

[0044] If the coefficient of variation of the mass per unit length of the carbon fiber bundle is 0.5% or less, when the carbon fiber bundle is used to manufacture a composite material, a good composite material with small deviation of tensile strength caused by the part can be obtained, and the amount of carbon fiber bundle used can be suppressed. It should be noted that the parameters related to the mass per unit length (g / m) of the carbon fiber bundle, that is, the mass per unit length (g / m) of the carbon fiber bundle and the coefficient of variation of the mass per unit length of the carbon fiber bundle can be controlled by using the method for manufacturing a carbon fiber bundle of the present invention described later.

[0045] The number of fluffs when unwinding the carbon fiber bundle of the present invention is preferably 1.5 pieces / m or less, more preferably 1.0 pieces / m or less, and further preferably 0.5 pieces / m or less. When a pressure vessel is made by FW molding, fluff is generated due to friction with the holes and metal rods in the process. If the fluff is rolled up and the accumulated fluff is molded, it will become a starting point for fracture, resulting in a tank strength lower than expected. By suppressing the generation of fluff in the process, a composite material with good tensile strength can be obtained. It should be noted that the number of fluffs when unwinding the carbon fiber bundle can be controlled by using the method for manufacturing the carbon fiber bundle of the present invention described later. It should be noted that the lower limit of the number of fluffs is ideally 0.0 pieces / m, but even if it is 0.1 pieces / m, there will be no practical problems.

[0046] The average single fiber diameter d (μm) of the carbon fiber bundle of the present invention is preferably 6.0 μm or more, more preferably 6.5 μm or more. When the composite material is manufactured by the FW method or the tow impregnation, since the impregnation depends on the single fiber diameter, the composite material can be efficiently manufactured by the large single fiber diameter. If the average single fiber diameter d is 6.0 μm or more, it can be satisfied from the perspective of impregnation. The upper limit of the average single fiber diameter d is not particularly limited. The larger the single fiber diameter, the more significant the deterioration of the dual structure formed in the flame retardant process. Therefore, the average single fiber diameter d is preferably less than 8.0 μm.

[0047] The blackened thickness K of the single fiber cross section of the carbon fiber bundle of the present invention is preferably 0.38 times or more of the aforementioned average single fiber diameter d, that is, 0.38×d or more, and more preferably 0.39×d or more. The blackened layer of the outer peripheral portion of the cross section perpendicular to the fiber axis of the carbon fiber single fiber is a region where the orientation degree of the crystal part is high and the tensile modulus is high. The thicker the blackened thickness K can be, the easier it is to suppress the internal and external structural differences when the average single fiber fineness is increased. When the internal and external structural differences are suppressed, the bundle strength and bundle elastic modulus of the carbon fiber are improved, so the quality of the carbon fiber can be improved by increasing the blackened thickness K.

[0048] If the blackening thickness K is 0.38×d or more, the proportion of the blackening layer in the single fiber cross section is 94% or more, and the carbon fiber becomes uniform, which satisfies the quality. The upper limit of K is 0.5×d when the single fiber cross section is entirely blackened, but it is sufficient to set the upper limit to 0.45×d.

[0049] The crystal orientation degree Π of the carbon fiber bundle of the present invention is preferably 79.5% or more, more preferably 80.0% or more. The elastic modulus of the strand of carbon fiber can be improved by increasing the crystal orientation degree in the carbon fiber bundle. If the crystal orientation degree Π is 79.5% or more, the elastic modulus of the strand can be satisfied from the viewpoint of quality. There is no particular upper limit, but it is practical to set it to 84% or less from the viewpoint of balancing manufacturing cost and performance.

[0050] In addition, this parameter can be controlled by using the method for producing a carbon fiber bundle of the present invention described later.

[0051] For the carbon fiber bundle of the present invention, it is preferred that the average single fiber diameter d (μm) is 6.0 or more and less than 8.0, the blackening thickness K of the single fiber cross section is 0.38×d or more, and the crystal orientation degree Π is 79.5% or more. By satisfying these three parameters at the same time, a composite material with particularly excellent tensile strength can be obtained.

[0052] With respect to the carbon fiber bundle of the present invention, when the ratio (Ri / Ro) of the crystallinity Ri of the inner layer of a single fiber obtained by Raman spectroscopy to the crystallinity Ro of the outer layer is set to Rr (hereinafter sometimes recorded as "the ratio of the inner and outer layers of crystallinity Rr"), Rr is preferably less than 1.03, and more preferably less than 1.01. The ratio of the inner and outer layers of crystallinity Rr is an indicator showing the degree of distribution of crystallinity within the diameter of a single fiber. The more uniform the crystallinity in the cross section, the smaller the Rr, and if the crystallinity is not uniform, the value becomes larger. When the ratio of the inner and outer layers of crystallinity Rr is smaller, a carbon fiber that is more uniform in diameter than conventional carbon fibers and in which tensile stress is not easily concentrated on the surface can be obtained, and the strength of the bundle can be improved. When the ratio of the inner and outer layers of crystallinity Rr is greater than 1.03, stress concentration occurs at the surface layer, which may lead to a decrease in the quality of the carbon fiber. As the lower limit of Rr, it is preferably greater than 1.00.

[0053] As for the means for achieving the inner-outer layer ratio Rr of the crystallinity of the carbon fiber bundle, any means may be used as long as it can be achieved within the aforementioned numerical range, but it is particularly preferred to use a method in which the initial stage of the flame retardant process is carried out at a low temperature together with low stretching in the spinning process and high stretching in the firing process.

[0054] The carbon fiber bundle of the present invention has excellent stability in mass per unit length (g / m), so when used for composite material molding, a carbon fiber reinforced composite material with high tensile strength can be obtained. In addition, by using the carbon fiber bundle of the present invention, a carbon fiber reinforced composite material with high tensile strength and small deviation in mass per unit length (g / m) can be easily obtained.

[0055] Next, a method for producing a carbon fiber bundle suitable for obtaining the carbon fiber bundle of the present invention will be described more specifically with reference to examples.

[0056] As a raw material for the production of carbon fiber precursor fiber bundles, polyacrylonitrile polymers are preferably used. It should be noted that in the present invention, polyacrylonitrile polymers refer to polymers in which acrylonitrile is the main constituent of the polymer skeleton. The main constituent refers to the constituent that accounts for 90 to 100% by mass of the polymer skeleton. In the production of carbon fiber precursor fiber bundles, polyacrylonitrile polymers preferably contain copolymer components from the perspective of smoothly carrying out the flame retardant step described later and controlling the high-grade carbon fiber.

[0057] As the monomer that can be used as the copolymerization component, from the viewpoint of promoting flame retardancy, it is preferred to use one or more monomers containing a carboxylic acid group or an amide group. For example, as the monomer containing a carboxylic acid group, acrylic acid, methacrylic acid, itaconic acid and their alkali metal salts, and ammonium salts can be mentioned. In addition, as the monomer containing an amide group, acrylamide can be mentioned.

[0058] In the production of the carbon fiber precursor fiber bundle, as a method for producing the polyacrylonitrile-based polymer, a method can be selected from known polymerization methods.

[0059] When manufacturing a carbon fiber precursor fiber bundle, the spinning method can use any of the dry-wet spinning method and the wet spinning method, but it is preferred to use the dry-wet spinning method which is beneficial to the knot strength of the obtained carbon fiber bundle. The spinning process includes: a spinning process, which uses the dry-wet spinning method to discharge the spinning solution from the spinning spinneret into a coagulation bath for spinning; a water washing process, which washes the fibers obtained in the spinning process in a water bath; a water bath stretching process, which stretches the fibers obtained in the water washing process in a water bath; and a dry heat treatment process, which performs dry heat treatment on the fibers obtained in the water bath stretching process, and may also include a steam stretching process for steam stretching the fibers obtained in the dry heat treatment process as needed. In addition, as needed, it is preferred to include a yarn combining process to make the number of filaments of the carbon fiber bundle consistent. It should be noted that the order of each process can also be appropriately exchanged.

[0060] The spinning solution is a solution obtained by dissolving the aforementioned polyacrylonitrile polymer in a solvent such as dimethyl sulfoxide, dimethylformamide, and dimethylacetamide in which polyacrylonitrile is soluble.

[0061] The coagulation bath preferably contains a solvent such as dimethyl sulfoxide, dimethylformamide, and dimethylacetamide used as a solvent for the spinning solution, and a coagulation-promoting component. As the coagulation-promoting component, a component that does not dissolve the polyacrylonitrile polymer and is compatible with the solvent used for the spinning solution can be used. Specifically, water is preferably used as the coagulation-promoting component.

[0062] As the water washing bath in the water washing step, it is preferred to use a water washing bath including multiple stages with a temperature of 30 to 98°C.

[0063] The stretching ratio in the water bath stretching step is preferably 2 to 6 times.

[0064] After the water bath stretching step, the fiber bundle is preferably provided with a silicone-containing oil agent for the purpose of preventing the single fibers from fusing together. The silicone oil agent is preferably a modified silicone, and preferably an oil agent containing amino-modified silicone having high heat resistance.

[0065] A known method can be used for the drying heat treatment step, and for example, the drying temperature is 100 to 200°C.

[0066] The aforementioned water washing step, water bath stretching step, oil agent application step, and dry heat treatment step can be performed to obtain a carbon fiber precursor fiber bundle suitable for obtaining the carbon fiber bundle of the present invention. It should be noted that, although steam stretching can be performed after the dry heat treatment step, the mass per unit length (g / m) of the carbon fiber precursor fiber bundle may vary.

[0067] The number of filaments in the carbon fiber precursor fiber bundle is preferably 6,000 or more, more preferably 12,000 or more, in a manner consistent with the number of filaments in the carbon fiber bundle. As an upper limit, there is no particular restriction, but it is preferably 36,000 or less. By being consistent with the number of filaments in the carbon fiber bundle, it is easy to eliminate the gaps between the single fibers in the carbon fiber bundle, the so-called fiber cracking. The more filaments in the carbon fiber precursor fiber bundle, the easier it is to reduce the deviation in the physical properties of the carbon fiber bundle. Therefore, it is preferred to use a spinneret having a spinneret hole number of 6,000 or less, for example, a spinneret hole number of 300 to 6,000, and to sew the carbon fiber precursor fiber bundle in a manner such that the number of filaments in the carbon fiber bundle is 6,000 to 36,000.

[0068] It should be noted that from the perspective of improving the strength of the wire bundle and the elastic modulus of the wire bundle, the single fiber fineness of the carbon fiber precursor fiber bundle is preferably 1.4 to 3.4 dtex, and more preferably 1.9 to 2.8 dtex. If it is 1.4 dtex or more, it can be satisfied from the perspective of productivity. The upper limit of the single fiber fineness is not particularly limited, but the larger the single fiber fineness, the more difficult it is to control the internal and external structural difference in the flame retardant process, which makes it easier for the quality of the carbon fiber to decrease. Therefore, the single fiber fineness is preferably 3.4 dtex or less.

[0069] In addition, the crystal orientation degree of the carbon fiber precursor fiber bundle is preferably 70.0 to 87.0%. The lower limit is more preferably 80% or more. The lower the orientation degree of the carbon fiber precursor fiber bundle, the more it can improve the stretchability in the flame retardant process. Therefore, if the orientation degree of the carbon fiber precursor fiber bundle is 87.0% or less, it can be fully stretched in the flame retardant process, and the tensile modulus of the carbon fiber bundle can be improved and the deviation of the mass per unit length (g / m) of the carbon fiber bundle can be reduced. It is more preferably 85.0% or less. In the case of less than 70%, the carbon fiber becomes a low orientation degree, which may lead to a decrease in the tensile modulus.

[0070] As for the means for achieving the orientation degree of the carbon fiber bundle, any means can be used as long as it can be achieved within the aforementioned numerical range, but it is particularly preferred to use a means of performing water bath stretching instead of steam stretching in the production of the carbon fiber precursor fiber bundle.

[0071] In the method for producing a carbon fiber bundle, a carbon fiber precursor fiber bundle is subjected to a flame retardant step, a preliminary carbonization step, and a carbonization step to obtain a carbon fiber bundle.

[0072] In order to improve the strand strength and strand elastic modulus of the carbon fiber and reduce the deviation of the mass per unit length (g / m) of the carbon fiber bundle, when the carbon fiber precursor fiber bundle is supplied to the flame retardant process, it is preferred to control the flame retardant treatment while stretching at a draw ratio of 1.30 to 3.00. A further preferred draw ratio is 1.60 to 2.40. By stretching in the flame retardant process, a low draw of less than 3 times can be performed for a long time of 5 seconds to 1,200 seconds, so that sufficient time can be spent on stretching, and the deviation of the mass per unit length (g / m) is not easy to increase. In the present invention, the draw ratio of the flame retardant process refers to the ratio of the speed of the carbon fiber flame retardant filament bundle after the final flame retardant furnace to the speed of the carbon fiber precursor bundle before the first flame retardant furnace. In the case of multiple flame retardant furnaces, the draw ratio can be distributed, but in order to simultaneously achieve the control of the internal and external structural differences, it is preferred to stretch in the first flame retardant furnace. Furthermore, when the stretching ratio can be distributed among the plurality of yarn passes constituting the flame retardant furnace, it is preferred to perform stretching in the first pass, and it is more preferred to perform stretching at a stretching ratio of at least 80%.

[0073] In order to improve the strand strength and strand elastic modulus of the carbon fiber, when the carbon fiber precursor fiber bundle is subjected to the flame retardant step, the infrared spectrum of the flame retardant fiber obtained is 1,453 cm -1 The peak intensity relative to 1,370 cm -1 The peak intensity ratio ([1,453cm -1 Peak intensity of] / [1,370cm -1 For convenience, the peak intensity ratio is referred to as "IR peak intensity ratio A") in the range of 0.60 to 0.65 and the IR spectrum at 1,254 cm -1 The peak intensity relative to 1,370 cm -1 The peak intensity ratio ([1,254cm -1 Peak intensity of] / [1,370cm -1 For convenience, the ratio of the peak intensities is referred to as "IR peak intensity ratio B") and is preferably controlled so as to be in the range of 0.70 to 0.80.

[0074] 1,453 cm in the infrared spectrum -1 The peak at 1,370 cm is derived from olefins and decreases as flame retardancy progresses. -1 The peak and 1,254cm -1The peaks are derived from flame retardant structures (considered to be naphthyridine ring and hydrogenated naphthyridine ring structures, respectively), and increase as flame retardant treatment proceeds. Usually, in the flame retardant treatment process, the peak derived from polyacrylonitrile is reduced as much as possible to increase the carbonization yield, but in the present invention, the conditions of the flame retardant treatment process are set in such a way that a large amount of olefins remain. By subjecting a flame retardant fiber bundle having such a structure to a pre-carbonization process, a carbon fiber bundle of the present invention can be obtained.

[0075] Furthermore, it is important to set the flame retardant conditions so that the IR peak intensity ratio B becomes 0.70 to 0.80. -1 The peak of is often seen in the part where flame retardancy is insufficient. If there are many such structures, the fracture toughness value is likely to decrease. The peak intensity ratio decreases as flame retardancy progresses, and the decrease is particularly significant in the initial stage. However, depending on the flame retardancy conditions, the peak intensity ratio may not reach below 0.80 even if the time is increased.

[0076] In order to achieve the two peak intensity ratios within the target range at the same time, the conditions should be set mainly with the following aspects in mind: less amount of copolymer components contained in the polyacrylonitrile polymer constituting the carbon fiber precursor fiber bundle; smaller fineness of the carbon fiber precursor fiber bundle; and higher flame retardant temperature in the second half.

[0077] Specifically, heat treatment may be performed until the IR peak intensity ratio A is in the range of 0.74 to 0.80 (first flame retardant step), and then heat treatment may be performed at a temperature higher than the first flame retardant step, until the IR peak intensity ratio A is in the range of 0.60 to 0.65 and the IR peak intensity ratio B is in the range of 0.70 to 0.80, for a flame retardant time of 5 to 25 minutes, preferably 5 to 15 minutes (second flame retardant step). In order to shorten the flame retardant time of the second flame retardant step, it is sufficient to increase the flame retardant temperature, but the appropriate flame retardant temperature depends on the characteristics of the carbon fiber precursor fiber bundle. In order to control within the above-mentioned infrared spectrum range, it is preferred that the center temperature of the carbon fiber precursor fiber bundle is preferably 250 to 300°C, more preferably 250 to 280°C, and further preferably 250 to 270°C.

[0078] The flame retardant temperature does not need to be constant, and a multi-stage temperature can also be set. When there are three or more flame retardant furnaces, the treatment with the second and subsequent flame retardant furnaces is called the second flame retardant process. It should be noted that in the present invention, there is no restriction on the number of flame retardant furnaces for the second flame retardant process. In order to improve the node strength of the obtained carbon fiber bundle, it is preferred to increase the flame retardant temperature and shorten the flame retardant time. Preferably, the first flame retardant process is preferably performed with a flame retardant time of 20 to 50 minutes, more preferably 30 to 40 minutes, and the flame retardant is performed at a flame retardant temperature within the above range.

[0079] The flame retardant time mentioned here refers to the time that the fiber bundle stays in the flame retardant furnace, and the flame retardant fiber bundle refers to the fiber bundle after the flame retardant process and before the pre-carbonization process. In addition, the peak intensity described here refers to the absorbance at each wavelength after a small amount of sampling of the flame retardant fiber and baseline correction of the spectrum obtained by measuring the infrared spectrum, without special peak segmentation, etc. In addition, the sample is diluted with potassium bromide (KBr) so that the concentration becomes 0.67% by mass and measured. In this way, the infrared spectrum is measured every time the flame retardant condition setting is changed, and the condition study can be carried out according to the preferred manufacturing method described later. By properly controlling the infrared spectrum peak intensity ratio of the flame retardant fiber, the internal and external structure difference and fracture toughness value of the obtained carbon fiber bundle can be controlled.

[0080] In the present invention, the flame retardant step refers to heat-treating the carbon fiber precursor fiber bundle at 200 to 300° C. in an atmosphere containing oxygen.

[0081] The total treatment time of the flame retardant step can be appropriately selected within the range of preferably 35 to 60 minutes, and more preferably within the range of 35 to 55 minutes.

[0082] In the pre-carbonization step of pre-carbonizing the fiber bundle obtained in the flame retardant step, it is preferred that the obtained flame retardant fiber be heat-treated in an inert atmosphere at a maximum temperature of 500 to 1,000°C. The stretching ratio of the pre-carbonization step is preferably 1.00 to 1.20, and more preferably 1.03 to 1.10. In this temperature range, microstructural defects caused by stretching are not easily generated. When the stretching ratio of the pre-carbonization step is 1.00 or more, the formation reaction of the initial carbonization structure between molecules inside the fiber can be promoted to form a dense fiber structure. Therefore, as a result, the knot strength of the carbon fiber bundle can be improved. If the stretching ratio of the pre-carbonization step is greater than 1.20, high tension is sometimes applied to the pre-carbonized fiber bundle to generate fuzz.

[0083] The specific gravity of the fiber bundle obtained through the preliminary carbonization step is preferably 1.5 to 1.8.

[0084] The pre-carbonized fiber bundle is carbonized in an inert atmosphere at a maximum temperature of 1,000 to 2,000°C. From the viewpoint of increasing the elastic modulus of the bundle, the higher the maximum temperature of the carbonization process, the better. However, if it is too high, the knot strength may be reduced. Therefore, the maximum temperature may be set by taking both into consideration. A more preferred maximum temperature is 1,100 to 1,800°C, and a further preferred maximum temperature is 1,200 to 1,600°C.

[0085] The carbon fiber bundle obtained as described above is preferably subjected to electrolytic surface treatment. The oxygen-containing functional groups are introduced into the carbon fiber bundle by performing electrolytic surface treatment. For the electrolytic surface treatment in the present invention, gas phase oxidation, liquid phase oxidation and liquid phase electrolytic oxidation can be used, but liquid phase electrolytic oxidation is preferably used from the viewpoint of high productivity and uniform treatment. In the present invention, there is no particular limitation on the method of liquid phase electrolytic oxidation, and it can be carried out by a known method.

[0086] After the electrolysis treatment, a sizing treatment may be performed to impart bundling properties to the obtained carbon fiber bundles. The sizing agent may be selected appropriately according to the type of matrix resin used in the composite material and has good compatibility with the matrix resin.

[0087] The amount of the sizing agent adhered is preferably 0.2 mass % or more and 1.0 mass % or less.

[0088] The process of making the tow preg using the carbon fiber bundle of the present invention can utilize a known method. For example, a tow preg manufacturing device equipped with a creel, a wet roller, a nip roller, and a winder is used. After coating one side of the carbon fiber bundle with an epoxy resin composition adjusted to a temperature of 20 to 60°C, the epoxy resin composition is passed through a nip roller, so that the epoxy resin composition can be impregnated into the inside of the reinforcing fiber bundle to obtain a tow preg. At this time, for the bobbin of the tow preg, 2,300m can be wound on a paper tube in a cylindrical manner with an initial tension of 600 to 1,000gf, a winding ratio of 6 to 10, and a winding width of 230 to 260mm.

[0089] In addition, the production process of carbon fiber reinforced composite materials using tow impregnation can utilize known methods. For example, as a method for producing a pressure vessel, a 7.5L polyethylene liner is set on a filament winding molding device, and the tow impregnation is wound around the entire liner. As the first layer, a ring layer at an angle of +89° relative to the axial direction of the liner and a ring layer at an angle of -89° relative to the axial direction of the liner are wound in a manner that their thickness becomes 1.4mm. Next, as the second layer, a spiral layer at an angle of +20° relative to the axial direction of the liner and a spiral layer at -20° relative to the axial direction of the liner are wound in a manner that their thickness becomes 2.2mm. Further, as the third layer, a method for obtaining an intermediate can be cited in which a ring layer at an angle of +89° relative to the axial direction of the liner and a ring layer at -89° relative to the axial direction of the liner are wound in a manner that their thickness becomes 0.6mm. In addition, as a curing method, there is a method in which the intermediate body is rotated in a curing furnace and cured at 150° C. for 4 hours to obtain a pressure vessel.

[0090] The methods for measuring various physical property values ​​used in the present invention are as follows.

[0091] <Carbon fiber bundle tensile test>

[0092] The wire harness strength, wire harness elastic modulus and elongation are determined according to the resin impregnation wire harness test method of JIS R7608:2004 in accordance with the following steps. As the resin formula, "CELLOXIDE" (registered trademark) 2021P (manufactured by Daicel) / boron trifluoride monoethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) / acetone = 100 / 3 / 4 (parts by mass) are used, and as the curing conditions, normal pressure, temperature of 125°C and time of 30 minutes are used. The wire harness of 7 carbon fibers is measured, and the average value is used as the wire harness strength, wire harness elastic modulus and elongation. It should be noted that the strain range when calculating the wire harness elastic modulus is 0.1 to 0.6%.

[0093] <Average single fiber diameter d of carbon fiber bundle>

[0094] For a carbon fiber bundle containing a plurality of carbon fiber filaments to be measured, the mass A per unit length is calculated. f (g / m) and density B f (g / cm 3 The number of filaments in the measured carbon fiber bundle is defined as C f The average single fiber diameter d (μm) of the carbon fiber is calculated by the following formula.

[0095] Average single fiber diameter of carbon fiber d (μm) = (1 / π × (A f / (B f / C f ))) (1 / 2) ×2×10 3 .

[0096] <Blackening thickness K and blackening layer ratio of the outer peripheral portion of the cross section perpendicular to the fiber axis of the carbon fiber single fiber>

[0097] The carbon fiber bundle to be measured is embedded in resin, and the cross section perpendicular to the fiber axis is ground. The cross section is observed at a total of 1,000 times using a 100x objective lens of an optical microscope. The blackening thickness is measured from the cross-sectional microscope image of the ground surface. Image analysis software ImageJ is used for analysis. First, in the single fiber cross-sectional image, black and white areas are segmented by binarization. For the brightness distribution within the cross section of the single fiber, the average value of the distribution is set as the threshold and binarization is performed. For the obtained binary image, the shortest distance from a point on the surface to the black-to-white drawn area is measured relative to the direction of the fiber diameter. The shortest distance is measured at 5 points within the circumference of the same single fiber, and the average value is calculated as the blackening thickness K at this level. In addition, the area of ​​the blackening thickness portion relative to the overall area of ​​the cross section of the carbon fiber single fiber perpendicular to the fiber axis, that is, the blackening layer ratio (%) is calculated by image analysis.

[0098] <Coefficient of variation of mass per unit length of carbon fiber bundle (%)>

[0099] The coefficient of variation (%) of the mass per unit length (g / m) of the carbon fiber bundle expressed by the ratio of the standard deviation to the average value ([standard deviation] / [average value]×100(%)) is measured as follows. The operation of cutting the carbon fiber bundle into 1 m length is repeated to prepare 10 carbon fiber bundle samples, and the mass (g) of each carbon fiber bundle sample is measured as the mass per unit length (g / m). Next, the average value and standard deviation of the mass per unit length of all 10 samples are calculated, and the ratio of the standard deviation to the average value is calculated to obtain a value expressed as a percentage ([standard deviation] / [average value]×100(%)).

[0100] <Crystal Orientation Degree of Carbon Fiber Precursor Fiber Bundle and Carbon Fiber Bundle (%)>

[0101] The degree of crystal orientation is measured as described below. Cut the fiber bundle into 40 mm lengths, accurately weigh 20 mg to collect the sample, align the sample in a manner that the sample fiber axis is accurately parallel, and use a sample adjustment fixture to adjust the sample fiber bundle to a uniform thickness of 1 mm. After impregnating with a dilute collodion solution and fixing it in a manner that does not destroy the shape, fix it on the sample stage of a wide-angle X-ray diffractometer (XRD-6100. (Shimadzu Corporation)). As an X-ray source, Cu Kα rays monochromatized by a Ni filter are used, and the degree of crystal orientation (%) is calculated using the following formula. It should be noted that in the case of a carbon fiber precursor fiber bundle, the half-value width (H°) of the profile extension in the meridian direction containing the highest intensity of diffraction observed near 2θ=17° is used, and in the case of a carbon fiber bundle, the half-value width (H°) of the profile extension in the meridian direction containing the highest intensity of diffraction observed near 2θ=25~26° is used.

[0102] Crystal orientation degree (%) = [(180-H) / 180] × 100

[0103] Here, H is the aforementioned half-value width.

[0104] <Ratio Rr of the crystallinity Ri of the inner layer to the crystallinity Ro of the outer layer of a single fiber of carbon fiber determined by Raman spectroscopy (inner-outer layer ratio Rr of crystallinity)>

[0105] The determination method of crystallinity distribution based on Raman spectroscopy is as follows. After embedding the carbon fiber with epoxy resin and wet grinding, it is observed. The spot diameter of the Raman microprobe used is about 1μm. In order to further improve the position resolution, the carbon fiber is grinded at an angle. The inclination angle of the grinding surface is 3° relative to the fiber axis. It should be noted that since the carbon fiber bundle is grinded at an angle, the depth from the surface corresponding to the measurement position is calculated as described below. It should be noted that when the cross section of the carbon fiber orthogonal to the fiber axis is a circle, the grinding surface is an ellipse.

[0106] Depth of measurement = sinθ×e

[0107] Here, e is the distance from the end of the long axis of the ground carbon fiber surface, and θ is the inclination angle of the fiber. In addition, when a and b are respectively set as the length of the long axis and the length of the short axis in the ground carbon fiber surface, it can be expressed as sinθ=b / a. It should be noted that the length a of the long axis in the ground carbon fiber surface refers to the length of the long side of the rectangle with the minimum area circumscribed to the ground carbon fiber surface, and the length b of the short axis refers to the length of the short side of the circumscribed rectangle. In the case where the cross section of the carbon fiber orthogonal to the fiber axis is not a circle, the depth from the surface corresponding to the measurement position is calculated as described below.

[0108] Determination depth = e × c / a

[0109] Here, a and c are respectively the length of the major axis and the length of the minor axis in the surface of the carbon fiber obtained by wet grinding after embedding the carbon fiber perpendicularly to the grinding surface with epoxy resin. It should be noted that the length a of the major axis in the surface of the carbon fiber obtained by grinding refers to the length of the long side of the rectangle with the minimum area circumscribed to the surface of the carbon fiber obtained by grinding, and the length b of the minor axis refers to the length of the short side of the circumscribed rectangle.

[0110] In addition, as the parameters of the Raman band, the following parameters are obtained: 1480 / I 1580 As a parameter of crystallinity. 1350 ,I 1480 ,I 1580 They are:

[0111] I 1350 : 1,350cm -1 The intensity of the Raman bands near

[0112] I 1580 : 1,580cm -1 The intensity of the Raman bands near

[0113] I 1480: 1,580cm -1 Nearby and 1,350cm -1 The valleys of the two Raman bands (appearing at about 1,480 cm -1 nearby) intensity.

[0114] The crystalline inner and outer layer ratio Rr is determined as follows.

[0115] In the single fiber cross section, the I 1480 / I 1580 Ro, and the I of the region within 0.5 μm from the center of the single fiber cross section 1480 / I 1580 Let Ri be the value and calculate it by the following formula.

[0116] Rr=Ri / Ro.

[0117] For the measurement of Raman band intensity, the two ends of the measurement range of the obtained graph were connected with a straight line and the background was subtracted, and the peak wave number of 1,350 cm was used as the reference wave number. -1 and 1,580cm -1 ±50cm -1 The peaks are fitted in the way they appear, and the peak intensity of each peak is determined. The Voigt function is used as the peak fitting function. In addition, the intensity of the valley between the two peaks is calculated. Each of the five single fibers in the same carbon fiber bundle is measured once, and the simple average is used. The measuring device uses a laser Raman spectrophotometer (Japan SCO Corporation NRS-3200), and the objective lens: 100 times is used. Beam diameter: 1μm, laser power: 2.5~3.2mW, wavelength: 532nm, measurement time: 120 seconds, measurement range: 1,200~1,900cm -1 .

[0118] <Number of fuzz when unwinding carbon fiber bundle>

[0119] The bobbin of the carbon fiber bundle was set on a creel, pulled by a roller at a tension of 1.6 mN / dtex and 5 m / min, and wound by a winder. At this time, the fluff generated between the creel and the roller was counted for 1 minute.

[0120] The number of fluffs (pieces / m) when the carbon fiber bundle is unwound = the counted number of fluffs (pieces) / 5 (m).

[0121] <Infrared spectrum intensity ratio>

[0122] 1,453 cm in the infrared spectrum -1 The peak intensity relative to 1,370 cm -1The ratio of the peak intensities of 1,254 cm-1 in the infrared spectrum (IR peak intensity ratio A) is -1 Peak intensity relative to 1,370 cm -1 The ratio of the peak intensities of (IR peak intensity ratio B) was calculated by the following method.

[0123] The flame-resistant fiber to be measured was freeze-crushed and 2 mg was accurately weighed and collected, which was thoroughly mixed with 300 mg of potassium bromide (KBr), placed in a molding jig, and pressurized at 40 MPa for 2 minutes using a press to prepare a tablet for measurement. The tablet was placed in a Fourier transform infrared spectrophotometer and the concentration was 1,000 to 2,000 cm -1 It should be noted that the background correction was performed by making the spectrum within the range of 1,700 to 2,000 cm -1 The minimum value in the range of is 0, and this is performed by subtracting the minimum value from each intensity. It should be noted that Paragon 1000 manufactured by PerkinElmer was used as the Fourier transform infrared spectrophotometer.

[0124] <Evaluation method of scalability (scalability evaluation)>

[0125] Two metal rods (stainless steel) with a diameter of 50 mm and a surface roughness Rmax of 0.3 μm were arranged in the vertical direction at an interval of 150 mm, and the carbon fiber bundle was in contact with each metal rod at an angle of 0.3925π (rad) ± 0.04π (rad), a total of 0.785π (rad). Then, the carbon fiber bundle was mounted on the metal rod, and the unwinding tension from the package was set to 800 g. The metal rod was pulled at 4 m / min by a driving roller, and after the second metal rod passed, a CCD transmission laser sensor / IG1500 manufactured by KEYENCE was set at a position of 15 mm, and the width of the carbon fiber bundle was measured at 120 points at 1 second intervals for 120 consecutive seconds, and its coefficient of variation ([standard deviation] / [average value] × 100 (%)) was used as the extensibility.

[0126] In the present invention, the preferred range of the expansion width was evaluated in four stages according to the following criteria.

[0127] S: coefficient of variation less than 0.5%

[0128] A: The coefficient of variation is 0.5% or more and less than 1.0%

[0129] B: The coefficient of variation is 1.0% or more and less than 5%

[0130] C: The coefficient of variation is 5% or more.

[0131] <Process passability of carbon fiber bundles (Process passability (fluff))>

[0132] Two metal rods (made of stainless steel) with a diameter of 50 mm and a surface roughness Rmax of 0.3 μm were placed in the vertical direction at an interval of 150 mm, and the carbon fiber bundle was in contact with and passed through each metal rod at an angle of 0.3925π (rad) ± 0.04π (rad), a total of 0.785π (rad). Then, the carbon fiber bundle was mounted on the metal rod, the unwinding tension from the package was set to 800 g, and the carbon fiber bundle was pulled at a speed of 4 m / min by a driving roller, and the aforementioned metal rod was passed. The number of fluffs per minute after passing through the second metal rod was counted, and converted to per 1 m using the following formula as the process passability. The process passability of the carbon fiber bundle was measured three times, and the arithmetic mean value was taken as the process fluff number (pieces / m) of the carbon fiber bundle.

[0133] Number of process fluffs of carbon fiber bundle (pieces / m) = the number of counted fluffs (pieces) / 4 (m)

[0134] S: The number of process hairs is less than 2.5 pieces / m

[0135] A: The number of process hairs is greater than 2.5 pieces / m and less than 3.5 pieces / m

[0136] B: The number of process fluff is greater than 3.5 pieces / m and less than 5.0 pieces / m

[0137] C: The number of process hairs is greater than 5.0 pieces / m

[0138] Example

[0139] (Example 1)

[0140] A copolymer containing 99.5 mol% of acrylonitrile and 0.5 mol% of itaconic acid was polymerized by a solution polymerization method using dimethyl sulfoxide as a solvent to obtain a spinning solution containing a polyacrylonitrile copolymer. The obtained spinning solution was temporarily discharged into the air from a spinning spinneret and introduced into a coagulation bath obtained from a 35 mass% aqueous solution of dimethyl sulfoxide controlled at 3° C. by a dry-wet spinning method to obtain a coagulated filament.

[0141] The coagulated filaments were washed with water by conventional methods and stretched in a water bath at a stretching ratio of 3.5 times. Next, the fiber bundle after water bath stretching was given an amino-modified silicone-based silicone oil agent and dried and densified using a heating roller at 160°C. The total stretching ratio for spinning was set to 3.5 times to obtain a carbon fiber precursor fiber bundle with 12,000 filaments. The single fiber fineness of the obtained carbon fiber precursor fiber bundle was 2.1 dtex and the crystal orientation degree was 84.0%.

[0142] Next, the first flame retardant process was performed under the conditions of a flame retardant temperature of 240° C. and a flame retardant time of 29 minutes, and the carbon fiber precursor fiber bundle was stretched at a draw ratio of 1.6 in an oven in an air atmosphere. The second flame retardant process was performed under the conditions of a flame retardant temperature of 263° C. and a flame retardant time of 14 minutes, and the fiber was flame retardant treated while being stretched at a draw ratio of 1.0, to obtain the flame retardant fiber bundle shown in Table 1.

[0143] The obtained flame-resistant fiber bundle is stretched and pre-carbonized in a nitrogen atmosphere at a maximum temperature of 800°C to obtain a pre-carbonized fiber bundle. The obtained pre-carbonized fiber bundle is stretched and pre-carbonized in a nitrogen atmosphere at a maximum temperature of 1,350°C. An aqueous sulfuric acid solution is used as an electrolyte, and the obtained carbon fiber bundle is subjected to an electrolytic surface treatment with an amount of 6 coulombs per 1g of carbon fiber. Next, the carbon fiber subjected to the electrolytic surface treatment is washed with water, dried in heated air at 150°C to remove water, and then, a 10-mol ethylene oxide adduct of bisphenol A is given as a sizing agent, and heat-treated at a temperature of 210°C for 75 seconds to obtain a carbon fiber bundle. The average single fiber diameter d of the carbon fiber bundle produced under the above conditions was 7.0 μm, the blackening thickness K was 2.5 μm, the crystal orientation degree Π was 79.6%, the sizing agent adhesion amount was 0.6 mass%, the coefficient of variation of the mass per unit length (g / m) was 0.25%, and the number of fluffs when unwinding was 3.0 pieces / m. The results are shown in Table 1.

[0144] (Example 2)

[0145] In the flame retardant step, the first flame retardant step was set to a flame retardant temperature of 238° C. and a flame retardant time of 31 minutes, and the second flame retardant step was set to a flame retardant temperature of 263° C. and a flame retardant time of 14 minutes to obtain a flame retardant fiber bundle. A carbon fiber bundle was obtained by the same method as in Example 1, except that the flame retardant fiber bundle was obtained.

[0146] (Example 3)

[0147] In the flame retardant step, the first flame retardant step was set to a flame retardant temperature of 235° C. and a flame retardant time of 37 minutes, and the second flame retardant step was set to a flame retardant temperature of 263° C. and a flame retardant time of 14 minutes to obtain a flame retardant fiber bundle. A carbon fiber bundle was obtained by the same method as in Example 1, except that the flame retardant fiber bundle was obtained.

[0148] (Example 4)

[0149] In the flame retardant step, the first flame retardant step was set to a flame retardant temperature of 238° C. and a flame retardant time of 31 minutes, and the second flame retardant step was set to a flame retardant temperature of 268° C. and a flame retardant time of 11 minutes to obtain a flame retardant fiber bundle. A carbon fiber bundle was obtained by the same method as in Example 1, except that the flame retardant fiber bundle was obtained.

[0150] (Example 5)

[0151] In the flame retardant step, the first flame retardant step was set to a flame retardant temperature of 235° C. and a flame retardant time of 37 minutes, and the second flame retardant step was set to a flame retardant temperature of 268° C. and a flame retardant time of 11 minutes to obtain a flame retardant fiber bundle. A carbon fiber bundle was obtained by the same method as in Example 1, except that the flame retardant fiber bundle was obtained.

[0152] (Example 6)

[0153] A carbon fiber precursor fiber bundle having a single fiber fineness of 1.7 dtex and a crystal orientation degree of 87.0% was obtained by the same method as in Example 1 except that the discharge amount of the spinning stock solution from the spinneret was changed. Next, the carbon fiber precursor fiber bundle was subjected to flame retardant treatment in an oven in an air atmosphere as a first flame retardant step at a flame retardant temperature of 240° C., a flame retardant time of 29 minutes, and a stretching ratio of 1.3, and then, as a second flame retardant step, the flame retardant fiber bundle was stretched at a flame retardant temperature of 263° C., a flame retardant time of 14 minutes, and a stretching ratio of 1.0 to obtain a flame retardant fiber bundle. The flame retardant fiber bundle obtained was treated in the same method as in Example 1 to obtain a carbon fiber bundle.

[0154] (Example 7)

[0155] In the flame retardant step, the first flame retardant step was set to a flame retardant temperature of 235° C. and a flame retardant time of 37 minutes, and the second flame retardant step was set to a flame retardant temperature of 263° C. and a flame retardant time of 14 minutes to obtain a flame retardant fiber bundle. A carbon fiber bundle was obtained by the same method as in Example 6, except that the above-mentioned method was used to obtain a flame retardant fiber bundle.

[0156] (Example 8)

[0157] In the flame retardant process, the first flame retardant process was set to a flame retardant temperature of 235° C. and a flame retardant time of 37 minutes, and the second flame retardant process was set to a flame retardant temperature of 268° C. and a flame retardant time of 11 minutes to obtain a flame retardant fiber bundle. A carbon fiber bundle was obtained by the same method as in Example 6, except that the flame retardant fiber bundle was obtained.

[0158] (Comparative Example 1)

[0159] In the flame retardant step, the first flame retardant step was set to a flame retardant temperature of 243° C. and a flame retardant time of 24 minutes, and the second flame retardant step was set to a flame retardant temperature of 263° C. and a flame retardant time of 14 minutes to obtain a flame retardant fiber bundle. A carbon fiber bundle was obtained by the same method as in Example 1, except that the above-mentioned conditions were adopted.

[0160] (Comparative Example 2)

[0161] In the flame retardant step, the first flame retardant step was set to a flame retardant temperature of 247° C. and a flame retardant time of 19 minutes, and the second flame retardant step was set to a flame retardant temperature of 268° C. and a flame retardant time of 14 minutes to obtain a flame retardant fiber bundle. A carbon fiber bundle was obtained by the same method as in Example 1, except that the flame retardant fiber bundle was obtained.

[0162] (Comparative Example 3)

[0163] A carbon fiber precursor fiber bundle having a single fiber fineness of 1.1 dtex and a crystal orientation degree of 89.0% was obtained by the same method as in Example 1 except that the discharge amount of the spinning stock solution from the spinneret was changed and that the fiber bundle was stretched 3.7 times in pressurized steam after drying and densification treatment to make the total stretch ratio of spinning 13 times. Next, the carbon fiber precursor fiber bundle was subjected to a flame retardant treatment in an oven in an air atmosphere at a flame retardant temperature of 253° C., a flame retardant time of 14 minutes, and a stretch ratio of 0.9 as a first flame retardant step, and then, as a second flame retardant step, it was stretched and subjected to a flame retardant treatment at a flame retardant temperature of 263° C., a flame retardant time of 14 minutes, and a stretch ratio of 1.0 to obtain a flame retardant fiber bundle. The flame retardant fiber bundle obtained was treated in the same method as in Example 1 to obtain a carbon fiber bundle.

[0164] [Table 1]

[0165]

[0166] Industrial Applicability

[0167] The present invention controls the drawing ratio in the spinning process and the flame retardant process, and treats at an appropriate temperature in the initial stage of flame retardant treatment, thereby being able to produce carbon fibers having a small variation in the mass per unit length (g / m) of the carbon fiber bundle and simultaneously satisfying excellent wire bundle tensile strength and tensile elastic modulus. The carbon fiber bundle obtained in the present invention can take advantage of this feature and is suitable for sports applications such as aircraft, automobile, and ship parts, golf shafts, and fishing rods, and general industrial applications such as pressure vessels.

Claims

1. A carbon fiber bundle, wherein the resin-impregnated bundle has a tensile strength of 4.5 to 6.5 GPa, a tensile elastic modulus of 205 to 270 GPa, the number of filaments is 6,000 to 36,000, and the coefficient of variation of the mass per unit length (g / m) of the carbon fiber bundle represented by the ratio of the standard deviation to the average value ([standard deviation] / [average value]×100(%)) is 0.00 to 0.5%.

2. The carbon fiber bundle according to claim 1, wherein The average single fiber diameter d (unit: μm) of the carbon fiber is 6.0 μm or more and less than 8.0 μm, and The blackened thickness K (unit: μm) of the carbon fiber is 0.38×d or more, and The carbon fiber bundle has a crystal orientation degree π of 79.5% or more.

3. The carbon fiber bundle according to claim 1 or 2, wherein: When the ratio (Ri / Ro) of the crystallinity Ri of the inner layer and the crystallinity Ro of the outer layer of the single fiber obtained by Raman spectroscopy is defined as Rr, Rr is 1.03 or less.

4. The carbon fiber bundle according to claim 1 or 2, wherein: The number of fuzz when the carbon fiber bundle is unwound is 1.5 pieces / m or less.

5. A tow preg using the carbon fiber bundle according to claim 1 or 2.

6. A carbon fiber reinforced composite material using the carbon fiber bundle according to claim 1 or 2.

7. A pressure vessel using the carbon fiber bundle according to claim 1 or 2.

8. A method for producing a carbon fiber bundle, which is a method for producing the carbon fiber bundle according to claim 1 or 2, wherein: A carbon fiber precursor fiber bundle having a single fiber fineness of 1.4 to 3.4 dtex is subjected to flame retardant treatment while being stretched at a draw ratio of 1.30 to 3.00 to obtain a flame retardant fiber bundle, and then the flame retardant fiber bundle is heat treated at 1,200 to 3,000° C. in an inert atmosphere to obtain a carbon fiber bundle.

9. The method for producing a carbon fiber bundle according to claim 8, wherein: The flame retardant treatment includes two steps of treatment. In the first flame retardant step, the infrared spectrum is 1,453 cm -1 The peak intensity relative to 1,370 cm -1 The flame retardant treatment is performed until the ratio of the peak intensity of the infrared spectrum to the peak intensity of the infrared spectrum is within the range of 0.74 to 0.

80. In the second flame retardant treatment step performed later than the first flame retardant treatment step, the peak intensity of the infrared spectrum is 1,453 cm -1 The peak intensity relative to 1,370 cm -1 The peak intensity ratio of 1,254 cm-1 in the infrared spectrum is in the range of 0.60 to 0.

65. -1 Peak intensity relative to 1,370 cm -1 The flame retardant treatment is performed until the ratio of the peak intensity of the carbon fiber to the carbon fiber falls within the range of 0.70 to 0.80, and the flame retardant fiber bundle obtained by the flame retardant treatment is heat-treated at 1,200 to 3,000° C. in an inert atmosphere to obtain a carbon fiber bundle.

Citation Information

Patent Citations

  • Flame-resistant fiber, carbon fiber and method for producing these fibers

    JP2004300600A

  • Method for producing flame-proofed fiber and carbon fiber

    JP2006283225A

  • Method for producing precursor fiber for carbon fiber and carbon fiber

    JP2009079343A

  • Carbon fiber bundle and manufacturing method therefor

    JP2017066580A

  • Towpreg manufacturing method

    JP2022519335A